Cardioprotective effect of transcutaneous electrical acupuncture point stimulation on perioperative elderly patients with coronary heart disease: a prospective, randomized, controlled clinical trial - Li H (Dove Medical Press, 2019)
Huizhou Li1, Chuan Wu1, Caizhen Yan2, Shuang Zhao1, Shuhong Yang1, Peng Liu1, Xin Liu1, Mingjie Wang1, Xiuli Wang1 1Department of Anesthesiology, Third Hospital of Hebei Medical University, Shijiazhuang, People’s Republic of China; 2Department of Pharmacology, Hebei Medical University, Shijiazhuang, People’s Republic of ChinaCorrespondence: Xiuli WangDepartment of Anesthesiology, Third Hospital of Hebei Medical University, No. 139 Ziqiang Road, Shijiazhuang, Hebei 050051, People’s Republic of ChinaTel +86 3 118 860 2172Email wangxiuli68@yeah.netPurpose: The purpose of this study was to evaluate the effects of transcutaneous electrical acupoint stimulation (TEAS) on postoperative autonomic nervous system function and serum biomarkers in the elderly.Patients and methods: A total of 122 American Society of Anesthesiologists class II or III patients with coronary heart disease undergoing spinal surgery were randomly divided into two groups: TEAS (received TEAS at Neiguan [PC6] and Ximen [PC4] for 30 minutes before anesthesia induction until the end of surgery) and control (received electrode plate at the same acupuncture points without any electrical stimulation). Serum was isolated for the measurement of concentration of high-sensitive troponin T (hs-cTnT), CRP, and CK. Heart rate (HR) and heart rate variability (HRV) including: total power (TP), low-frequency (LF) power, high-frequency (HF) power, and LF/HF ratio were used to assess autonomic nervous system function. The primary outcome was to evaluate whether TEAS changed the postoperative serum hs-cTnT. The secondary outcomes were to observe the effects of TEAS on HRV, circulating CK and CRP after surgery.Results: Hs-cTnT, CRP, and CK concentrations were significantly higher on first, third and fifth day after surgery than those before anesthesia induction in both groups. Hs-cTnT concentration was significantly lower on the first and third day after surgery in TEAS group than in control group. Compared with 1 day before surgery, TP, LF, and HF decreased significantly and HR, LF/HF increased significantly on first, third, and fifth day after surgery in control group. Compared with control group, HR was significantly lower on the first, third, and fifth day after surgery, LF/HF decreased and TP, LF, HF were significantly higher on the first day after surgery in TEAS group.Conclusion: TEAS at PC6 and PC4 could reduce postoperative serum hs-cTnT concentration and change HRV index to improve autonomic nervous system activity.Keywords: transcutaneous electric acupuncture point stimulation, coronary artery disease, autonomic nervous system, high-sensitive troponin T, heart rate variability